Estimating down time of glove dipping machines operation using Exponential and Weibull distributions - Nor Hamizah Miswan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Reliability of any particular component or system is very important as it involves the whole stage of the product life-cycle. It is necessary for a factory to ensure that down time is managed proactively to ensure efficient product manufacturing process. It is common for many manufacturing plants to conduct preventive and corrective maintenance because long machine repair time will cause loss of productivity and revenue. In order to minimize repair time, both inventory and workforce preparation are crucial. This paper uses statistical methods to determine proper time slots to conduct preventive maintenance of a machine. The proposed method determines Mean Time to Failure (MTTF) via Exponential and Weibull distributions using time to failure data of two sets of similar machines from glove manufacturing production line. Results revealed that Weibull distribution offered better MTTF prediction performance compared to Exponential distribution. By pairwise comparison, these two methods do not present significant difference, and hence, both methods could serve as the benchmark in designing potential preventive maintenance strategy.